Review of Nikos Andriotis, Πρόσφυγες στην Ελλάδα 1821-1940: Άφιξη, περίθαλψη, αποκατάσταση: [Refugees in Greece, 1821-1940: Arrival, care, settlement] - Salvanou, Emilia (Historein, 2025)
Review of Nikos Andriotis, Πρόσφυγες στην Ελλάδα 1821-1940: Άφιξη, περίθαλψη, αποκατάσταση [Refugees in Greece, 1821-1940: Arrival, care, settlement]. Athens: Foundation of the Hellenic Parliament, 2020. 387 pp.